Effect of Partially Protected Sodium Butyrate on Performance, Digestive Organs, Intestinal Villi and E. coli Development in Broilers Chickens - Chamba, F.; Puyalto , M.; Ortiz, A.; Torrealba, H.; Mallo, J.J.; Riboty, R. (International Journal of Poultry Science, 2014)
The aim of this study was to evaluate the effect of partially protected sodium butyrate (PSB) on performance, digestive organs, intestinal villi and E. coli development in broilers chickens. Nine hundred twenty four one-day-old mixed Cobb® chicks were divided in 3 treatments with 7 replicates each in a randomized block design. Treatment T1 was a control diet without any growth promoter, treatment T2 was the control diet plus colistin at 100,000 IU/kgBW and treatment T3 was the control diet with PSB at 700 ppm. Chicks were fed in mash form for 3 phases: starter (1-14 days), grower (15-28 days) and finisher (29-42 days). There were no significant differences on performance among all treatments in starter phase. Chicks fed PSB in grower and finisher phases had the highest weight gain and the best feed conversion ratio. Relative digestive organs weights were not affected by treatment in any phase. Jejunum and small intestine relative lengths of birds fed PSB and colistin at 14 days were longer than those of birds fed control diet. Jejunal villi of birds fed PSB and colistin at 42 days were higher than those in birds fed the control diet. Colistin produced the deepest crypts and the lowest villi height/crypt depth ratios in all intestinal segments at 14 days. Intestinal E. coli growth was not affected by any treatment. These data indicate that partially protected sodium butyrate and colistin improves performance, colistin as an antibiotic growth promoter and PSB by improving intestinal villi development in broilers chickens.